Реалізація замкнених 1-форм з замкненими рекурентними кривими на замкнених поверхнях - Будницька, Н.В. (Інститут математики НАН України, 2009)
The closed1-forms with isolated zeros and closed recurrent curves on closed surfaces are considered. The theorem of realization of such closed 1-forms is proved.